2011
DOI: 10.1021/nl200708y
|View full text |Cite
|
Sign up to set email alerts
|

Sn-Doped Hematite Nanostructures for Photoelectrochemical Water Splitting

Abstract: We report on the synthesis and characterization of Sn-doped hematite nanowires and nanocorals as well as their implementation as photoanodes for photoelectrochemical water splitting. The hematite nanowires were prepared on a fluorine-doped tin oxide (FTO) substrate by a hydrothermal method, followed by high temperature sintering in air to incorporate Sn, diffused from the FTO substrate, as a dopant. Sn-doped hematite nanocorals were prepared by the same method, by adding tin(IV) chloride as the Sn precursor. X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

78
1,077
5
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,027 publications
(1,181 citation statements)
references
References 41 publications
(91 reference statements)
78
1,077
5
4
Order By: Relevance
“…The lifetime of this phase is increased under high anodic bias conditions, assigned, as pre- viously, to slower electron/hole recombination due to enhanced electron depletion in the photoelectrode at such bias conditions (36). We note here that faster recombination phases are also likely (13,37,38) although not resolved in the studies reported herein. In addition, a slow (approximately 2-s) decay phase is observed, assigned to long-lived holes, whose amplitude increases with increasingly anodic bias.…”
Section: Resultsmentioning
confidence: 53%
“…The lifetime of this phase is increased under high anodic bias conditions, assigned, as pre- viously, to slower electron/hole recombination due to enhanced electron depletion in the photoelectrode at such bias conditions (36). We note here that faster recombination phases are also likely (13,37,38) although not resolved in the studies reported herein. In addition, a slow (approximately 2-s) decay phase is observed, assigned to long-lived holes, whose amplitude increases with increasingly anodic bias.…”
Section: Resultsmentioning
confidence: 53%
“…3b clearly validated their highest IPCE of 42.5% at 300 nm, which was strikingly higher than that of bulk ZnSe (0.25%), (Zn 2 Se 2 )(pa) (0.4%), ZnSe-pa octuple layers (4.3%), ZnSe-pa quadruple layers (5%) and ZnSe-pa double layers (12.1%). To the best of our knowledge, the photoconversion efficiency of 42.5% is much better than that of most existing reports 22,23 . This extraordinary IPCE of the ZnSe single layers could be attributed to their several clear-cut advantages including ultraflexible, large-area, atomic thickness and high (110) orientation, which would be detailedly discussed below.…”
Section: Characterizations Of Freestanding Znse Single Layersmentioning
confidence: 53%
“…Introducing substitutional doping elements or forming surface passivating layer are extensively recognized as efficient strategy to enhance the photoelectrochemical performance 5, 7. Herein we realize the Ti doped hematite and TiO 2 passivating layer on the surface of hematite nanorod and mpATO by a simple hydrothermal decomposition of TiCl 4 followed a postannealing process (see the Experimental Section for details).…”
Section: Resultsmentioning
confidence: 99%
“…Although the theoretical solar‐to‐hydrogen (STH) efficiency of hematite can reach to 15% if incorporate with a proper tandem photovoltaic (PV) setup,3 the performance of the state‐of‐the‐art hematite based photoelectrode is far from the idealized model, owing to the intrinsic adverse factors such as poor electrical conducting ability, restricted hole diffusion length (<5 nm), low absorption coefficient, and low flat‐band potential in water splitting. [[qv: 1b,4]] Much efforts have been devoted to addressing this issues including elemental doping,5 morphology tailoring,[[qv: 5e,6]] and surface modification 7…”
Section: Introductionmentioning
confidence: 99%